2019
DOI: 10.1136/sextrans-2018-053938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mass drug administration of azithromycin for trachoma elimination on prevalence and azithromycin resistance of genitalMycoplasma genitaliuminfection

Abstract: BackgroundMass drug administration (MDA) of 20 mg/kg (maximum 1 g in adults) azithromycin for ocular Chlamydia trachomatis (CT) infection is a key component of the WHO trachoma elimination strategy. However, this dose may be suboptimal in Mycoplasma genitalium infection and may encourage emergence of antimicrobial resistance (AMR) to azithromycin.ObjectivesTo determine the effect of MDA for trachoma elimination on M. genitalium prevalence, strain type and azithromycin resistance.MethodsA secondary analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…34 However, we did not find macrolide resistance associated mutations in 23S rRNA gene of MG strains, even though macrolide-resistance of MG was prevalent in the U.S. 35 and common worldwide. 36 Interestingly, we also previously described lack of macrolide resistant MG in the Solomon islands 37 despite a high prevalence of infection in the islands. Among the TV strains detected, 2/10 had the A238T SNP which results in a premature stop codon in the ntr6 gene that is associated with metronidazole resistance.…”
Section: Discussionmentioning
confidence: 67%
“…34 However, we did not find macrolide resistance associated mutations in 23S rRNA gene of MG strains, even though macrolide-resistance of MG was prevalent in the U.S. 35 and common worldwide. 36 Interestingly, we also previously described lack of macrolide resistant MG in the Solomon islands 37 despite a high prevalence of infection in the islands. Among the TV strains detected, 2/10 had the A238T SNP which results in a premature stop codon in the ntr6 gene that is associated with metronidazole resistance.…”
Section: Discussionmentioning
confidence: 67%
“…Almost 900 million doses of azithromycin have been distributed by trachoma control programmes since 1999 42 and in Amhara alone 15 million doses are administered every year. 3 Mass distribution of azithromycin is likely to become more common as more evidence emerges of off-target effects such as reducing infectious diseases, 23,[43][44][45] diarrheal diseases 46 and childhood mortality. 22,[47][48][49][50] There is concern about the impact of these programmes on development of antimicrobial resistance in Ct and other bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The highest prevalence has been reported among sex workers: 16% in Kenya ( 29 ) and 26% in Uganda ( 30 ). Data on M. genitalium infection among pregnant women remains limited despite the disease’s association with adverse pregnancy outcomes ( 26 ); available estimates range from 0.7%–0.9% in the United Kingdom and France ( 14 , 31 ) to 6.2% in Guinea-Bissau ( 32 ) and 11.9% in the Solomon Islands ( 15 ). More data on the prevalence and consequences of M. genitalium infection among pregnant women are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Regional data on M. genitalium in LMICs are limited. One study from the Solomon Islands examined the effects of mass drug administration (MDA) using 1 g of oral azithromycin for eliminating ocular C. trachomatis on M. genitalium infection rates ( 15 ). Before MDA, the study found an 11.9% (95% CI 8.3%–16.6%; n = 236) prevalence of M. genitalium among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation